Effect of V/Mo Ratio on Structural Properties of VxMo(1-x)Oy Nanoparticles used as Alkaline Fuel Cell Catalyzer - Beyribey, Berceste; Saygi, Berrin; Acikyildiz, Selen Ezgi; Culcu, Lusi; Mutlu, Bayram; Vardar, Duygu Sena; Sarac, Hanifi (TRANS TECH PUBLICATIONS LTD, 2014)
V0.3Mo0.7O3 and V0.6Mo0.4O3 nanoparticles were synthesized through reducing acidified vanadate and molybdate solution at around 60-70 degrees C. The catalysts are aimed to be used as anode in alkaline fuel cells. BET and SEM analysis are done to characterize the obtained particles. According to the SEM results, both compounds were formed in nanosized particles and BET results showed that BET surface area of V0.3Mo0.7O3 catalyst has 5 times higher than that of V0.6Mo0.4O3.
Keywords: Nanocatalyst; vanadium molybdenum oxide; alkaline fuel cell; non-precious metals; OXIDE; ELECTROCATALYSTS; COMPOSITE; Energy & Fuels; Engineering; Materials Science; Mechanics